Aktivitas Orang Tionghoa di Kesultanan Panai, Labuhan Bilik: Sebuah Kajian Historik - Yushar Tanjung (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2020)
This paper traces the presence and activities of the Chinese community in Labuhan Bilik, which was the center of the Panai Sultanate government which developed into a trading port after the Dutch colonial government developed economic activities in East Sumatra through the opening of plantations. Labuhan Bilik has developed so that it attracts the outside community to participate in trade activities, especially the Chinese community. They have been in Labuhan Bilik since 1875 and are active traders conducting trade transactions with traders in the Malay Peninsula and Singapore. Their presence received a welcome from the Panai Sultanate government and received protection in the intention of providing a place to live. The Dutch colonial government facilitated it by appointing their group members to become Kapitan who functioned as coordinators and liaisons with the government. Meanwhile, the Sultan approved the appointment of the citizens of the Sultanate to become Kerani for the Chinese community to connect them with the Sultanate. They successfully traded until Indonesia became independent during the Old Order. After that their activities faded along with the changing political and economic order in Indonesia so that they now do not play a role anymore because many have moved to other regions.